Internet usage among undergraduate dental students in India. - Kumar, Santhosh; Tadakamadla, Jyothi; Tibdewal, Harish; Duraiswamy, Prabu; Kulkarni, Suhas (Revista Odonto Ciencia, 2010)
Aim: To assess the internet usage among dental students at a private dental institution that would aid in designing and implementation of interactive online learning in the dental curriculum. Materials and methods: Internet usage among dental undergraduate students pursuing their career was assessed by using a questionnaire which consisted of nine multiple choice questions. Results: The total sample size accounted to 247 with an overall response rate of 66%. Only 5.7% and 4.05% used internet daily for general and dental purposes respectively. More than half the subjects (55.5%) never used internet for academic purposes in comparison to 9.3% for general use. Nearly half of the subjects preferred home for internet access followed by internet café and only 7.9% accessed internet in college. 60% of the subjects used search engines to access dental subjects, many clinical year subjects used search engines more than preclinical students (78% Vs 41.2%, P=0.001). Conclusions: Dental undergraduate students at a private dental institution in India have reported levels of internet use that were lesser than students in other nations which may be due to limited access and availability at the present institution, introduction of internet based education into existing curriculum is desirable which would enhance students' ability to acquire, appraise, and use information from the internet to solve health problems quickly and efficiently during training and practice.